Direct synthesis of high-quality nitrogen-doped graphene via ion implantation. (November 2018) - Zhao, Yunbiao; Wang, Xu; Fu, Engang; Han, Dong; Wang, Peipei; Wu, Zaoming; Chen, Yi; Chen, Yuhan; Zhao, Ziqiang
Abstract: Synthesis of nitrogen-doped graphene (NG) is of great importance and conventional synthesis methods still remain huge challenges due to uncontrollable nitrogen doping content and complicated experimental procedure. In this study, a promising approach for synthesis of high-quality NG via nitrogen ion implantation compatible with the current microelectronic industry is reported. By nitrogen ion implantation into a newly designed multilayered substrate (Ni/Cu/amorphous-SiC/SiO2 /Si), high-quality NG can be directly grown on the metal surface after a one-step rapid thermal processing. A detailed growth model of NG based on the design of multilayered substrate, the low energy ion implantation and the formation of Cu-Ni alloy with composition gradient is established. The ion implantation approach could open up a new pathway for doping graphene, as well as shed light on versatile and potential applications of doping other 2D materials. Graphical abstract: Image 1